Hormone therapy following surgery in low-grade endometrial stromal sarcoma: Is it related to a decrease in recurrence rate?. Issue 5 (May 2019) - Comert, Gunsu Kimyon; Turkmen, Osman; Kar, Irem; Yucel, Ozge; Kilic, Cigdem; Boran, Nurettin; Basaran, Derman; Karalok, Alper; Turan, Taner
Abstract : Background: Low-grade endometrial stromal sarcoma (LGESS) is, in most cases, a slow-growing malignancy; however, it is related with high recurrence rates. The aim of this study is to determine which factors may be associated with the recurrence rate of LGESS. Methods: The clinicopathological features and treatment options in 37 patients with LGESS were evaluated. Results: All patients underwent the hysterectomy and bilateral salpingo-oophorectomy. Additionally, lymphadenectomy was performed in 56.8% (n = 21) of the patients. Among the patients who underwent lymphadenectomy, 14.3% (n = 3) had lymph node metastasis. The disease was limited to the uterus in 75.7% of patients. Treatment following surgery was radiotherapy in three patients, chemotherapy in seven patients, hormone therapy in 12 patients, and chemotherapy plus hormone therapy in one patient. Megestrol acetate was used in all patients who received hormone therapy. Median follow-up time was 96 months. The 5-year disease-free survival and disease-specific survival were 72% and 97%, respectively. The recurrence rate was 27%. Only hormone therapy following surgery was significantly associated with a lower recurrence rate, even in patients with stage 1 disease. None of the patients treated with hormone therapy following surgery had recurrence, whereas recurrence occurred in 38.5% of the patients who underwent surgery only ( p = 0.039). Conclusion: Hormone therapy after surgery should be considered a viable option for decreasing the LGESS recurrence rate, regardless of the disease stage.